2019
DOI: 10.1177/0886109919851142
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Economic Abuse in the Community: Listening to Survivor Voices

Abstract: Economic abuse (EA) comprises tactics of intimate partner violence (IPV) which undermine survivors’ economic self-sufficiency and self-efficacy. Evidence is strong that survivors of IPV who have accessed formal services have experienced a wide range of EA tactics. However, there remains a gap in our understanding of EA experiences for survivors who have not sought IPV services. Thus, this article presents the findings of qualitative interviews with a group of women attending community college ( n = 20) who scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Cross-sectional studies of female IPV survivors propose women have fewer educational and employment opportunities, leading to lower income and greater financial instability, which, in turn, makes them vulnerable to economic abuse (Postmus et al, 2012; Weissman, 2020). Voth Schrag (2019) uses CCT to demonstrate how various abusive tactics enable an abusive male to control a female victim in such circumstances. The study found that micro-control of the victim led to a pattern of economically abusive behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Cross-sectional studies of female IPV survivors propose women have fewer educational and employment opportunities, leading to lower income and greater financial instability, which, in turn, makes them vulnerable to economic abuse (Postmus et al, 2012; Weissman, 2020). Voth Schrag (2019) uses CCT to demonstrate how various abusive tactics enable an abusive male to control a female victim in such circumstances. The study found that micro-control of the victim led to a pattern of economically abusive behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several scholarly works have examined economic abuse among low-income women who are victims of IPV (Adams et al, 2020; Anitha, 2019; Christy & Valandra, 2017; Postmus et al, 2020; Postmus et al, 2012; Stylianou et al, 2013; Stylianou, 2018a; Voth Schrag, 2019). Adams et al (2008) developed the Scale of Economic Abuse to study the phenomenon among female victims of physical, sexual, and emotional abuse.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…My aim in this study is to address two primary gaps in extant knowledge regarding intimate partner violence (IPV): first, that scholars have thus far focused more extensively on physical violence rather than psychological, emotional, and economic abuse; and second, that strategies provided by practitioners and helpline workers tend to be focused on help for those who leave, rather than directed toward those who choose to stay in the relationship (Stylianou 2018;Voth Schrag 2019). Contemporary research reveals a disparity in terms of how victims who make the decision to remain in a relationship with their abuser are treated.…”
Section: Literature Reviewmentioning
confidence: 99%